OP14 A systematic review of cost-effectiveness evaluations of psychological therapies for schizophrenia and bipolar disorder. (2nd September 2017) - Buck, D; Shields, GE; Elvidge, J; Hayhurst, K; Davies, LM
Abstract : Background: Schizophrenia and bipolar disorder (BD) are among the top twenty causes of disability. Costs of treatment and to society are substantial. NICE guidelines recommend psychological/psychosocial interventions are considered in response to acute episodes/recovery promotion. This review aims to assess cost-effectiveness of psychological interventions, determine robustness of the current evidence base, and identify evidence gaps. The key research question is: which psychological interventions are cost-effective, compared to usual care/alternative interventions, in schizophrenia or BD? Methods: Electronic searches of PsycINFO, MEDLINE and Embase identified economic evaluations relating incremental cost to outcomes in an Incremental Cost-Effectiveness Ratio (ICER) published in English since 2000. Studies had to include: probability of cost-effectiveness at explicitly-defined thresholds; adults with schizophrenia/BD; any psychological intervention (e.g. psychological therapy, Improving Access to Psychological Therapies, integrated/collaborative care). Comparators could be routine practice, no intervention, or alternative psychological therapies. Searches were performed in August 2015 (updated January 2017). There were two screening stages with explicit inclusion criteria applied by 2 reviewers at each stage. Pre-specified data extraction/critical appraisal were performed. Results were summarised qualitatively. The review is registered on the PROSPERO database of systematic reviews. Results: Of 3785 studies identified, 11 were included. All were integrated clinical and economic randomised controlled trials. All used cost-effectiveness and/or cost-utility analysis. The commonest intervention was CBT (6/11 studies). Measures of health benefit included QALYs (5/11), QLS 1/11), PANSS (2/11), MANSA (1/11), GAF (3/11), days with normal functioning (1/11), a working memory subscale (1/11), full vocational recovery (1/11), days with a bipolar episode (1/11). Follow-up ranged from 6 months to 5 years. 6/11 studies used provider perspectives for the primary analysis; the remainder considered societal perspectives. Interventions were cost-effective in most identified studies (9/11): ICERs ranged from dominant (intervention is cost-saving AND more effective) to £18 844 per QALY; the probability of cost-effectiveness ranged from 50% to 99.5% at chosen thresholds. The two studies deemed not cost-effective involved art/body psychotherapy and noted significant uncertainty in the data as a limitation. All studies had limitations, including missing data, sample sizes and challenges controlling for other medications/treatments received outside the trial intervention. Conclusion: Although recommended in clinical guidelines, there was limited evidence about the cost-effectiveness of psychological therapy for schizophrenia/BD. Most included studies concluded psychological interventions for schizophrenia/BD are cost-effective. However policy implications are unclear due to methodological limitations and heterogeneity in populations and settings between studies. The review had some limitations including potential for English-language bias and limited time-horizon.